2018
DOI: 10.1002/qj.3250
|View full text |Cite
|
Sign up to set email alerts
|

The precipitation response to variable terrain forcing over low mountain ranges in different weather regimes

Abstract: The impact of terrain forcing on cloud formation and precipitation over low mountain ranges is investigated by numerical experiments with the COnsortium for Small‐scale MOdeling (COSMO) model. The investigation comprises six case studies divided into strong and weak large‐scale synoptic forcing. To understand how the terrain affects the occurrence and intensity of precipitation, sensitivity runs with flattened mountains and incrementally smoothed terrain were performed at 500‐m horizontal grid spacing. On days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 51 publications
2
29
0
Order By: Relevance
“…In the analysis of factors that may affect the spatial patterns of the MP and EDP complexities, it is found that the altitude is a common constraint. Previous studies have shown that the topography can affect the formation and distribution of precipitation (Schneider et al ., 2018). This study shows that topography also has an impact on the complexity of precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…In the analysis of factors that may affect the spatial patterns of the MP and EDP complexities, it is found that the altitude is a common constraint. Previous studies have shown that the topography can affect the formation and distribution of precipitation (Schneider et al ., 2018). This study shows that topography also has an impact on the complexity of precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…This may create local instabilities and can be an issue when assessing the impact of topography on summer convection in a weak synoptic flow (e.g. Schneider et al, 2018). However, the fast large-scale background flow associated with Egon quickly ventilates the model and the relatively low sea-surface temperature in winter prevents spontaneous convective activity.…”
Section: Model Experimentsmentioning
confidence: 99%
“…It is a non-hydrostatic limited-area atmospheric prediction model, which operates on a rotated latitude/longitude grid with an Arakawa C-grid for horizontal differencing. First, simulations are performed with 2.8-km grid spacing on the operational COSMO-DE grid of the German Weather Service driven by 7 km COSMO-EU initial and boundary data (see Schneider et al (2018) for exact domain location).…”
Section: Numerical Modelmentioning
confidence: 99%
“…Land surface properties (e.g., land cover, terrain, and soil texture) are highly heterogeneous across a wide range of spatiotemporal scales (Santanello et al, 2018) and potential linkages between land surface variables and atmospheric variables such as temperature and precipitation are difficult to establish (e.g., Seneviratne et al, 2010). Over mountainous terrain, thermally induced wind systems and low-level convergence zones are crucial for the initiation of deep convection with prevailing weak winds (e.g., Schneider et al, 2018). They are often less well resolved in operational models, which limits the forecast capabilities in contrast to situations governed by large-scale synoptic forcing, when the forecast of precipitation is often more reliable (Baldauf et al, 2011).…”
Section: Introductionmentioning
confidence: 99%